2018
DOI: 10.1590/1414-431x20177035
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in rat rectus abdominis muscle induced by diabetes and pregnancy

Abstract: The urethral muscle of diabetic pregnant rats is affected by long-term mild diabetes and short-term severe diabetes, which plays a crucial role in the pathogenesis of pelvic floor disorders. We hypothesized that muscles outside the pelvis are subject to similar changes. The current study aimed at analyzing the effects of long-term mild and short-term severe diabetes on the structure and ultrastructure of fiber muscles and collagen in rats' rectus abdominis (RA) muscle. Therefore, the RA muscle of virgin, pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
1
31
0
1
Order By: Relevance
“…The consequences of UI persist not only during pregnancy but up to 2 years post-partum and have a negative impact on the quality of life [14,15]. Previously, our research group conducted studies on the urethral tissue obtained from a pregnant Streptozotocin (STZ) rat model [16][17][18][19][20][21]. The hyperglycemia status in these rats is manifested by STZinduced necrosis of the pancreatic β-cells [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The consequences of UI persist not only during pregnancy but up to 2 years post-partum and have a negative impact on the quality of life [14,15]. Previously, our research group conducted studies on the urethral tissue obtained from a pregnant Streptozotocin (STZ) rat model [16][17][18][19][20][21]. The hyperglycemia status in these rats is manifested by STZinduced necrosis of the pancreatic β-cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…A higher or lower hyperglycemic level caused an impairment of the urethral tissue [17,18,20]. We also investigated the changes in rectus abdominis muscle (RAM) in the same animal model and discovered that both the RAM and urethral muscles are subjected to similar morphological changes during diabetic myopathy [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, these experimental results demonstrated that both long-term mild hyperglycemia and short-term severe hyperglycemia negatively impacted the muscle health in rats. RAM is subjected to similar structural changes related to pregnant diabetic myopathy [25,26,28] with intramuscular transformation and reorganization in fiber types [30][31][32].…”
Section: Introductionmentioning
confidence: 99%